An examination of the role of film genre in the preservation of political and cultural memory of the struggle for freedom in South Africa : an analytical study of Sarafina - Masvopo, Demetria Thabisile (My University, 2021)
The study investigates the popular South African feature film entitled Safarina (1992) and its depiction of young South Africans’ resistance against the apartheid system during the 1970s through the 1980s. It analyses how Sarafina portrays the socio-cultural and political environment that characterised the apartheid modus operandi; explores the film’s ideological frames of societal dissent during apartheid and examines Sarafina’s cinema verité and application of symbolism in portraying the historical context and narrative of the South African struggle for freedom. The study refers to extensive literature about film as an artistic medium, dynamics in film genre, its role in representing societal dissent, application of filmic elements in technical production and relevance of symbolism in film criticism. The theoretical framework entails two theories, namely Framing and Ideological Film Criticism. The study adopted the qualitative descriptive case study design cognisant of its ability to provide a complex visual and audio-textual description of the events represented during the period under study. It used purposive sampling to select the film Sarafina to elucidate the contours and experiences of the apartheid system in pre-democratic South Africa. Methodological techniques used in the study involved audio-visual content analysis during the data collection process and thematic analysis from which discursive themes were generated and findings were derived. The findings of the study demonstrate the representational etiquette of Sarafina to bring out significant political and cultural memories of the struggle for freedom with potential to create conducive spaces for positive social, cultural and political benefits for the contemporary South African society. The study concludes by recommending the usage of Sarafina and other forms of film genre, not only as artefacts for preserving historical experiences, but also to promote active citizenship, good democratic governance, and effective service delivery in post-apartheid South Africa.
Thesis (M. A. (Media Studies)) -- University of Limpopo, 2021
Keywords: Film genre; Political-cultural memory; Apartheid; Sarafina; Film genres; Apartheid -- South Africa; Apartheid in art